Biological Behavior of Canine Acanthomatous Ameloblastoma Assessed With Computed Tomography and Histopathology: A Comparative Study. (September 2020) - Goldschmidt, Stephanie; Bell, Cynthia; Waller, Kenneth; Hetzel, Scott; Soukup, Jason W.
Canine acanthomatous ameloblastoma (CAA) appears to have variable biological behavior with some tumors presenting with slow growth and minimal bone loss while others grow rapidly and cause severe cancellous and cortical bone destruction. The primary aim of the study is to elucidate if variations (grades) of CAA can be identified based on both histological and diagnostic imaging indices, and to compare markers of more aggressive behavior between these 2 commonly used diagnostic tools. This study evaluated 45 cases of CAA and confirmed that there is high degree of variability in tumor invasiveness as measured with computed tomography, with predominantly intraosseous tumors being significantly associated with more invasive behavior. However, the analysis also identified that there was very little correlation between computed tomographic and histological appearance of the tumor. CAA tends to have a highly uniform and predictable histological pattern, with tumors that aggressively invade bone (as seen on CT) not showing features of atypia that might be helpful in predicting the biological behavior of the neoplastic cells. Thus, reliance on diagnostic imaging as a measure of biological behavior is recommended for treatment planning as well as possible creation of a variant/grading scheme. Prospective studies are required to evaluate if differing variants of CAA as based on diagnostic imaging should be treated differently, and how this would affect long term clinical outcome.